2019
DOI: 10.1080/22423982.2019.1612703
|View full text |Cite
|
Sign up to set email alerts
|

Exploring why and how encounters with the Norwegian health-care system can be considered culturally unsafe by North Sami-speaking patients and relatives: A qualitative study based on 11 interviews

Abstract: Background : Citizens of Norway have free and equal access to healthcare. Nurses are expected to be culturally sensitive and have cultural knowledge in encounters with patients. Culturally safe care is considered both a process and an outcome, evaluated by whether the patients feel safe, empowered and cared for, or not. All patients request equal access to quality care in Norway, also Sami patients. Objectives : The aim of the study is to identify whether Sami patients and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 23 publications
2
24
0
6
Order By: Relevance
“…A number of studies address similar themes, including one study of Sami patients in the Norwegian healthcare system that found a culturally unsafe environment and lack of interpreting services to be associated with patients receiving unequal access to health information. 7 Additionally, a study involving First Nations, Inuit and Métis participants in Canada showed how the legacy of colonialism as well as contemporary exposures to culturally unsafe care impacted how engaged patients felt with their diabetes management. 8 …”
Section: Introductionmentioning
confidence: 99%
“…A number of studies address similar themes, including one study of Sami patients in the Norwegian healthcare system that found a culturally unsafe environment and lack of interpreting services to be associated with patients receiving unequal access to health information. 7 Additionally, a study involving First Nations, Inuit and Métis participants in Canada showed how the legacy of colonialism as well as contemporary exposures to culturally unsafe care impacted how engaged patients felt with their diabetes management. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Å bruke pårørende som tolk kan imidlertid ha konsekvenser for pasientsikkerheten (Jensen et al, 2018;Mehus et al, 2018;2019;). Mehus et al (2019) fant at bruk av familiemedlemmer som tolk ofte blir brukt også innenfor det nordsamiske området. Deres studie indikerer at det å ha pårørende til å hjelpe brukeren med å huske og tyde budskap kan vaere helt nødvendig, men det innebaerer også begrensninger fordi informasjon kan selekteres, for eksempel på grunn av tabuer innen familien.…”
Section: Diskusjonunclassified
“…Samer kan imidlertid vaere mindre tilfreds med tjenestetilbudet (Dyregrov et al, 2014;Nystad et al, 2008;Stoor, 2016;Sørlie & Nergård, 2005). En viktig årsak til dette er at mange opplever å bli møtt av helsepersonell som mangler språk-og kulturforståelse (Angell et al, 2012;Josefsen, 2006;Mehus et al, 2019;NOU 2014: 8;Nystad et al, 2008). For de samiske pasientene kan møtet med helsetjenesten gjøre at de føler seg ensomme, isolert og frakoblet samisk språk og kultur (Mehus et al, 2019).…”
Section: Introduksjonunclassified
See 2 more Smart Citations